Analisis SWOT sebagai Strategi Efektif dalam Meningkatkan Keberhasilan Akreditasi Perpustakaan - Unyil Unyil; Pauzi Pauzi (Maktabatuna, 2025)
The purpose of this study is to analyze and describe SWOT Analysis as an Effective Strategy in Increasing the Success of Library Accreditation. The approach used is a qualitative descriptive method supported by IFAS and EFAS analysis and utilizing the SWOT approach to map the internal and external aspects of the library. The SWOT (Strengths-Weaknesses-Opportunities-Threats) study was carried out to assess the library as a whole, assess strengths and opportunities, and reduce weaknesses and threats. The results of the SWOT analysis supported by IFAS and EFAS, the facilities and infrastructure in the University X library are still not optimal, with limited facilities and inadequate internet access. The number of library visitors is also still low, the need for more effective promotional strategies, such as the use of social media and increasing the convenience of services. Strategies that can be applied include increasing the number of collections, optimizing services, strengthening governance, and utilizing digital technology in library promotion and services.